Smart Hydrogels for the Augmentation of Bone Regeneration by Endogenous Mesenchymal Progenitor Cell Recruitment. Issue 7 (5th February 2020) - Lienemann, Philipp S.; Vallmajo‐Martin, Queralt; Papageorgiou, Panagiota; Blache, Ulrich; Metzger, Stéphanie; Kiveliö, Anna‐Sofia; Milleret, Vincent; Sala, Ana; Hoehnel, Sylke; Roch, Aline; Reuten, Raphael; Koch, Manuel; et al.
Abstract: The treatment of bone defects with recombinant bone morphogenetic protein‐2 (BMP‐2) requires high doses precluding broad clinical application. Here, a bioengineering approach is presented that strongly improves low‐dose BMP‐2‐based bone regeneration by mobilizing healing‐associated mesenchymal progenitor cells (MPCs). Smart synthetic hydrogels are used to trap and study endogenous MPCs trafficking to bone defects. Hydrogel‐trapped and prospectively isolated MPCs differentiate into multiple lineages in vitro and form bone in vivo. In vitro screenings reveal that platelet‐derived growth factor BB (PDGF‐BB) strongly recruits prospective MPCs making it a promising candidate for the engineering of hydrogels that enrich endogenous MPCs in vivo. However, PDGF‐BB inhibits BMP‐2‐mediated osteogenesis both in vitro and in vivo. In contrast, smart two‐way dynamic release hydrogels with fast‐release of PDGF‐BB and sustained delivery of BMP‐2 beneficially promote the healing of bone defects. Collectively, it is shown that modulating the dynamics of endogenous progenitor cells in vivo by smart synthetic hydrogels significantly improves bone healing and holds great potential for other advanced applications in regenerative medicine. Abstract : Engineered biomaterials are used to trap and isolate bone progenitor cells during bone healing. Freshly isolated bone progenitor cells enable the identification of bioactive molecules that stimulate their recruitment. Identified recruitment‐stimulating molecules and bone morphogenetic protein are used to treat bone defects. Only the biomaterials‐controlled sequential, but not the simultaneous delivery of both factors improves bone healing.